PARADIGMA PENDEKATAN SISTEM DALAM KAJIAN HUKUM ISLAM MENURUT JASSER AUDA - Wendry, Novizal; Syafruddin, Syafruddin (Jurnal AL-AHKAM, 2020)
Usul al-fiqh and fiqh are a mechanism and a product of ijtihād were born in the Islamic classical period. Along with the times, this mechanism should adopt modern science so that the resulting of fiqh can answer the needs of the times. Jasser Auda is offering a systems approach in applying Islamic law. According to Auda, consideration needs maqashidī through the analysis of six features; cognitive nature, wholeness, openness, interrelated hierarchy, multi-dimensionality, and purposefulness. So that, Islamic jurisprudence can be validated by analyzing of these features till the humanist, justice, peace, care for the environment, and following of the development of science of Islamic jurisprudence can be realized